University at Albany President Karen Hitchcock... - Schmidt, Mark (Digital Media Department Records, 2002)
University at Albany President Karen Hitchcock recognizing Albany Mayor Jerry Jennings at the New York Giants VIP Breakfast held at the University at Albany. [20002156]